Efecto del extracto seco de passiflora incarnata l. sobre los niveles plasmáticos de ácido úrico en mus musculus var. swis con comportamiento psicótico - De La Puente Orellano, Anggelha Marytte (2016)
The purpose of this research was to evaluate the effect of dry extract of Passiflora incarnata L. on plasma uric acid levels as a marker of oxidative stress in Mus musculus var. SWIS with psychotic behavior using pharmacological models Open field, Rotad rod, and the enzymatic method for the determination of uric acid. Four groups (White, Control, Problem Problem I and II) worked. The target group received physiological saline 0.9% at a dose of 5 mL / kg intraperitoneally for 10 days, then distilled water was administered 10 mL / kg orally for two days; the control group were induced psychotic behavior with ketamine at a dose of 5 mg / kg intraperitoneally then distilled water was administered 10mL / kg orally for two days; to Problem groups I and Problem II were induced psychotic behavior with ketamine at a dose of 5 mg / kg intraperitoneally for ten days and were subsequently treated with Passiflora incarnata L. at a dose of 20 mg / kg and 80 mg / kg respectively orally for a period of two days. Ten days psychotic behavior of groups through the Open Field models and Rota rod was evaluated. The variables were analyzed in Open Field: square advanced, bipedal, preening, interference with holes and defecation; Rota rod was time spent on the rotating rod. A initiates the twelve days of treatment plasma uric acid levels were determined. The result obtained with the Open field model was an increase in square advanced (hyperlocomotion), comparing the target group with the other groups (p <0.05), showing the psychotic effect of ketamine. Rota rod relative to a statistically significant difference (p = 0.167) was observed, ketamine produces no motor incoordination. At the level of uric acid it was observed that no statistically significant difference (p = 0.001), buying the white group with the control group (ketamine), this shows that experimentally psychotic specimens there is an imbalance in oxidative balance, to buy control group (ketamine) with P1 and P2 (Passiflora incarnata L.) groups at doses 20 mg / kg, 80mg / kg respectively, statistically significant difference (p = 0.031) was found and (p = 0.002), both show a similar effect psychotic experimentally antioxidant specimens. We concluded that the dry extract of Passiflora incarnata L. normalizes uric acid levels in experimentally psychotic specimens, however additional studies are needed